Termoskop dan Pendingin Udara Sederhana: Pengembangan Alat Peraga Fisika Untuk Pembelajaran Fisika - Marscella, Fitri Anggi; Komikesari, Happy; Fakhri, Jamal; Dewi, Pramita Sylvia (Universitas Islam Negeri Raden Intan Lampung, 2019)
Abstract: This research is background because learners do not understand the concept of physics with daily events, there is no tool to support the teaching and learning process. The use of simple physics props is expected to improve the learning outcomes of learners and can understand the concept by connecting the daily events in human life in physics. This study aims to find out how to develop physics props and the feasibility of simple physics aids for learning of thermodynamics to learners' learning outcomes. This research uses qualitative and quantitative approach, while the type of this research is research and development. Data collection technique is using questionnaire. Data analysis techniques to test the feasibility of props using Likert scale. Based on the results of data analysis using the likert scale statistic test, SMA Negeri 1 Sidomulyo get the percentage of eligibility of 82.925%